Artificial synthetic MnIVCa–oxido complexes mimic the oxygen-evolving complex in photosystem II1. Issue 10 (14th March 2015) - Chen, Changhui; Zhang, Chunxi; Dong, Hongxing; Zhao, Jingquan
<x xml:space="preserve">Abstract</x> Artificial synthetic MnIVCa–oxido complexes containing reactive water molecules have been synthesized to mimic the oxygen-evolving center in photosystem II.